Experience of a health day at the university of Namibia: A community service - Kloppers, J.M.; Nelumbu, L.N.; Nauiseb, T.; Tibinyane, P. Angula. M.B.; Sumpi, N.G. (International Journal of Medicine, 2015)
The School of Nursing and Public Health conducted an annual health day at the main campus in Windhoek. The clinic on campus was not operational, at this time. This service is much appreciated by students and staff. The Community Health Nursing lecturers and second year diploma students participated in the Health day. The services that were rendered included blood pressure; weight and height and body mass index; blood-glucose test; eye test; neck massage. Health education on HIV/AIDS and cancer prevention was given to those who took part. The health day targeted non-communicable diseases (NCD) in order to promote prevention strategies. NCD is a medical condition or disease that can be defined as non-infectious and non-transmissible among people. It is further described as chronic diseases which last for long periods of time and progress slowly. Sometimes, NCDs result in rapid deaths as seen in certain types of diseases such as autoimmune diseases, heart diseases, stroke, most cancers, asthma, diabetes, chronic kidney disease, osteoporosis, Alzheimer's disease, cataracts, and many more (World Health Organization (WHO).Aim: The health day was done to promote and to provide necessary information and to raise awareness to students and staff on their health and on how to prevent non –communicable diseases.Method: No actual research was done.Results: Data analysis was done based on the findings from the users of the service. The total number of the people who used the blood pressure service were 161. Of which 38 were found to have high blood pressure while 10 were found with low blood pressure and were advised to visit the hospital or clinic and 113 had normal blood pressure. Many people, who were detected with high blood pressure, or hypertension, had no idea of having it. The people who came for weight were 130 out of which 63 had normal weight, 32 were overweight, 16 were obese, and 15 were underweight. Health education was given on nutrition, specifically on balance diet. 20 people were found with high blood-glucose level ranging between 7-21.8 mml. Total number of people who attend eye test were 63 of which 4 had poor vision and were referred to eye clinic. Neck massage attracted many people, and they enjoyed it.Conclusion: The results of health day indicated the need of such services in order to detect abnormalities and to improve the knowledge and understanding of the community members on non-communicable diseases and how to prevent them.